An Emerging Role for PI5P in T Cell Biology - Nunes, Jacques A.; Guittard, Geoffrey (Frontiers in Immunology, 2013)
Phosphoinositides are critical regulators in cell biology. Phosphatidylinositol 4,5-bisphosphate, also known as PI(4,5)P2 or PIP2, was the first variety of phosphoinositide to enter in the T cell signaling scene. Phosphatidylinositol bis-phosphates are the substrates for different types of enzymes such as phospholipases C (β and γ isoforms) and phosphoinositide 3-kinases (PI3K class IA and IB) that are largely involved in signal transduction. However until recently, only a few studies highlighted phosphatidylinositol monophosphates as signaling molecules. This was mostly due to the difficulty of detection of some of these phosphoinositides, such as phosphatidylinositol 5-phosphate, also known as PI5P. Some compelling evidence argues for a role of PI5P in cell signaling and/or cell trafficking. Recently, we reported the detection of a PI5P increase upon TCR triggering. Here, we describe the current knowledge of the role of PI5P in T cell signaling. The future challenges that will be important to achieve in order to fully characterize the role of PI5P in T cell biology, will be discussed.